SOFT TISSUE LASER APPLICATIONS AND ITS EFFECTS IN PEDIATRIC DENTISTRY - literature review - Grămadă Elena; Gamen-Tărăboanță Andra; Alexa Ioan Vlăduț; Lucaci-Ciuhat Oana; Dorneanu Andreea; Toma Vasilica; Sîrghe Ana Elena; Vacariu Simina Mădălina (Romanian Dental Association for Education, 2021)
Objectives: The purpose of this review was to evaluate the literature on the applications and results for soft tissue of the laser therapy in pediatric dentistry. Material and method: An electronic search was performed in the PubMed, ProQuest, Medline and Google Scholar databases, using MeSH terms. Results: Laser-assisted therapy can offer new treatment possibilities, simplify dental procedures, reduce postoperative sensitivity and the need for postoperative medication due to laser-induced biostimulation and anti-inflammatory and analgesic effects. All wavelengths produce incision and vaporization of oral tissues, along with a high bactericidal and hemostatic effect. Conclusions: The laser offers innovative, fast, minimally invasive and painless therapies for children's oral soft tissues. Laser treatment for soft tissue includes labial, lingual phrenectomy, operculectomy, gingivectomy / gingivoplasty, excisional removal of oral pathologies with biopsy and treatment of aphthous stomatitis and herpes lesions.